2003
DOI: 10.1177/0310057x0303100406
|View full text |Cite
|
Sign up to set email alerts
|

Cricoid Pressure Training: How Useful are Descriptions of Force?

Abstract: Cricoid pressure has been used for over 200 years. During that time, training in the technique has not changed greatly, despite the well-documented potential for complications if performed improperly. Typically, training relies on quantitative or qualitative descriptions such as "firm" pressure, a number of Newtons of force or equivalent force to that causing pain while pressing on the nose. This study tests the value of these descriptive methods in training to apply cricoid pressure. Fifty subjects were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…None of the patients experienced regurgitation or vomiting when the pressure was applied, and 3 patients had immediate reflux into the pharynx upon release of the pressure after tracheal intubation. 81,82 In his report, Sellick described the use of "firm" pressure but did not quantify the actual force needed to occlude the esophagus or how this force could be reproduced in the clinical setting. 3 Since then, CP has been considered the lynchpin of RSII and the expected standard of care during anesthesia induction for patients at high risk of aspiration.…”
Section: The Cp Controversymentioning
confidence: 99%
See 1 more Smart Citation
“…None of the patients experienced regurgitation or vomiting when the pressure was applied, and 3 patients had immediate reflux into the pharynx upon release of the pressure after tracheal intubation. 81,82 In his report, Sellick described the use of "firm" pressure but did not quantify the actual force needed to occlude the esophagus or how this force could be reproduced in the clinical setting. 3 Since then, CP has been considered the lynchpin of RSII and the expected standard of care during anesthesia induction for patients at high risk of aspiration.…”
Section: The Cp Controversymentioning
confidence: 99%
“…Whereas some authors strongly endorse the technique and believe in its effectiveness, 99 others believe that CP should be abandoned because it adds to patients' risks with no evidence of any gained benefit. 22,82 22,82 …”
Section: The Cp Controversymentioning
confidence: 99%
“…Many authors accept the value of 1 kg being equivalent to 9.81 N. A simple approximation is 1 kg 5 10 N. Furthermore, a consensus has been made that application of cricoid cartilage pressure to the conscious patient should be 1 kg to 2 kg or 10 N to 20 N. Once the patient becomes unconscious, pressure should increase to 3 kg to 4 kg or 30 N to 40 N. Forty-four N should reasonably protect patients from aspiration. 4,9,[23][24][25][26][27][28][29] Controversial Aspects of Cricoid Pressure…”
Section: Management Of the ''At-risk'' Patientmentioning
confidence: 99%
“…It has been shown among anaesthetic staff that commonly used descriptors of cricoid force are inadequate, knowledge of the prescribed force is poor, as few as 20% are able to achieve the prescribed range, and furthermore, that despite effective training in its application, cricoid force remains a skill that is poorly retained. 4,[6][7][8][9][10][11][12][13] To achieve its purpose in preventing gastropharyngeal regurgitation and aspiration applied cricoid force must occlude the oesophageus at the level of the cricoid cartilage, maintaining an effective upper oesophageal pressure in excess of intragastric pressure. It has been demonstrated that the upper oesophagus can be occluded by the correct application of cricoid force at or in excess of 30 newtons (N).…”
Section: Introductionmentioning
confidence: 99%